WEDM process parameters optimization by preference-based CS & PSO algorithm for LCP - Jain, Shubham; Parashar, Vishal (Materials and manufacturing processes, 2023)
Locking Compression Plates (LCP) are typically made of Ti6Al4V alloy. LCP is used to heal fractures of the bone. This article uses Wire Cut Electric Discharge Machining (WEDM) to machine Ti6Al4V alloy. Responses are optimized by two metaheuristic algorithms, the cuckoo search algorithm (CS) and particle swarm optimization (PSO). The cuckoo search algorithm shows that the maximum MRR is 59.4312 mg/min & the maximum cutting speed is 5.0625 mm/min. The single-objective PSO shows a maximum MRR of 59.3632 mg/min & the maximum cutting speed is 5.0155 mm/min. The GRA revealed that the optimum weight for MRR and cutting speed is 48.868% and 51.132% respectively. Scanning electron microscope analysis indicates proper biocompatibility after machining. This article compares CS and PSO with similar calculations for the t-test and found that the p-values for MRR and Cutting speed are 0.9432 and 0.9919.